A rare case of mediastinal liposarcoma: Multidisciplinary approach and clinical challenges - Fadila Kouhen; Oussama Afandi; Najwa Benslima; Othmane Bensalah; Meryem Naciri; Hanae El Gouach; Othmane Kaanouch; Hafsa Chahdi; Youssef Mahdi; Bouchra Daher (Radiology Case Reports)
Mediastinal liposarcomas are rare, aggressive tumors that represent a small proportion of mediastinal masses and present significant diagnostic and therapeutic challenges due to their proximity to vital structures. This case report details a 58-year-old female who presented with progressive dyspnea and chest pain, initially attributed to more common causes. However, further investigation, including thoracic CT scan, revealed a 15 cm anterior mediastinal mass with pericardial effusion. Biopsy and histopathological examination confirmed the diagnosis of dedifferentiated liposarcoma (DDL). Given the tumor's large size and proximity to critical structures, surgical resection was initially deemed unresectable, and the patient was started on neoadjuvant chemotherapy (EIM regimen). However, despite tumor progression after chemotherapy, the patient underwent successful surgical resection with narrow margins. Postsurgery, the patient received adjuvant radiotherapy to reduce the risk of local recurrence. Despite mild side effects such as acute esophagitis during radiotherapy, the patient showed no signs of disease recurrence at the 12-month follow-up. This case highlights the challenges in diagnosing and managing mediastinal liposarcomas and demonstrates a multimodal treatment approach, including chemotherapy, surgery, and radiotherapy, which can lead to favorable short-term outcomes.